Developing Smart Building Learning Media (Knx System) and its Impacts on Student’s Learning Outcomes - Hardiyanto, Resqi; Zuhrie, M. Syariffudien; Rusimamto, Puput Wanarti; Harimurti, Rina; Achmad, Fendi (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study investigated the developments of Smart Building learning media (KNX System) which focuses on control system elements at SMK Negeri 3 Surabaya, assessed through three aspects: (1) media validity, (2) media practicality, and (3) media effectiveness. This research uses the Research & Development (R&D) development method using the Borg & Gall model. Validity assessments included trainer validity tests, module validity tests, validity tests of student response questionnaires, validity tests of pretest and posttest, validity tests of attitude observation sheets and skills observation sheet tests. The results of the validity test showed that this trainer scored 86%, the validity test of the module scored 81%, the validity test of the student response questionnaire scored 77%, the validity test of the pretest and posttest questions got a score of 75%, the validity test of the attitude observation sheet scored 76%, and the validity test of the skill observation sheet scored 74%. Next, a practicality test was carried out which resulted in a score of 69%, in the practice category. For the latter, an effectiveness test was performed to assess how effectively the treatment is applied. The result of the N-Gain score obtained a value of 0.5, which was in the interval of 0.3 ≤ n ≤ 0.7. This indicated that the average N-Gain score is categorized as moderate. To differentiate between the average score of the pretest and posttest, the Paired Sample T-Test was performed using SPSS, resulting in a p value of 0.000. This indicated a significant influence on student learning outcomes before and after the implementation of this learning media. It can be concluded that the learning media developed is suitable for use in learning and can be used as a reference for the development of learning media in other learning elements.